2004
DOI: 10.1002/jcc.20110
|View full text |Cite
|
Sign up to set email alerts
|

Using quaternions to calculate RMSD

Abstract: A widely used way to compare the structures of biomolecules or solid bodies is to translate and rotate one structure with respect to the other to minimize the root-mean-square deviation (RMSD). We present a simple derivation, based on quaternions, for the optimal solid body transformation (rotation-translation) that minimizes the RMSD between two sets of vectors. We prove that the quaternion method is equivalent to the well-known formula due to Kabsch. We analyze the various cases that may arise, and give a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
343
0
6

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 325 publications
(351 citation statements)
references
References 20 publications
2
343
0
6
Order By: Relevance
“…The rotation matrix for optimal superimposition was calculated using the quaternion method developed by us previously. 15,16 To calculate the rotation matrix, the alpha carbons of the residues 8-127 for FT and 11-130 for TFL1 were superimposed excluding the external loop and its C-terminal region because the crystal structures of FT and TFL1 are similar and the major structural difference occurs at the external loop. Using the calculated rotation matrix, the whole protein structures were superimposed, and then RMSD was calculated between the alpha carbon coordinates at equivalent positions.…”
Section: Methodsmentioning
confidence: 99%
“…The rotation matrix for optimal superimposition was calculated using the quaternion method developed by us previously. 15,16 To calculate the rotation matrix, the alpha carbons of the residues 8-127 for FT and 11-130 for TFL1 were superimposed excluding the external loop and its C-terminal region because the crystal structures of FT and TFL1 are similar and the major structural difference occurs at the external loop. Using the calculated rotation matrix, the whole protein structures were superimposed, and then RMSD was calculated between the alpha carbon coordinates at equivalent positions.…”
Section: Methodsmentioning
confidence: 99%
“…The RMSD represented the structural changes during the simulation [47,48]. Analysis for the time evolution-RMSD resulted from the simulation at 300K and revealed that the structure was fluctuated at around 4 to 6 Å from the initial structure, as shown in Fig.…”
Section: Conformational Dynamics Of Dna Pol I Itb-1mentioning
confidence: 99%
“…The MaxSub score is the three dimensional similarity between two protein structures. The learning algorithm can be extended easily to predict ranks based on additional similarity measures such as the RMSD score [8], the GDT score [11], and the TM score [10]. However, we have decided to use the MaxSub score due to the high correlation among these similarity scores.…”
Section: A Data and Preprocessingmentioning
confidence: 99%
“…Related model quality assessment programs [3]- [7] are based on machine learning algorithm. The learning algorithm learns a function that maps a combination of a set of features extracted form the computationally generated structures to a quality score such as the RMSD score [8], the MaxSub score [9], the TM score [10], and the GDT score [11]. The developers of these methods formulated the problem as a regression problem.…”
Section: Introductionmentioning
confidence: 99%